An Event‐Related Potential (ERP) Investigation of Filler‐Gap Processing in Native and Second Language Speakers. Issue 4 (4th October 2013) - Dallas, Andrea; DeDe, Gayle; Nicol, Janet
Abstract : The current study employed a neuro‐imaging technique, Event‐Related Potentials (ERP), to investigate real‐time processing of sentences containing filler‐gap dependencies by late‐learning speakers of English as a second language (L2) with a Chinese native language background. An individual differences approach was also taken to examine the role of proficiency and working memory. Materials included a plausibility manipulation to look at whether a plausibility effect, the N400 effect, was found at the point of resolution, the verb, in filler‐gap dependencies. The results suggest that, although the L2 speakers as a group are not sensitive to plausibility variations, correlational analysis indicates that more proficient L2 speakers, like the first‐language (L1) speakers, are sensitive to plausibility variations while processing filler‐gap sentences. Working memory was not found to be associated with more native‐like processing of these constructions.